Can Memory and Truth Be Tailored by Law? Memory Law and the Right to the Truth in Rwanda (Politeja, 2023)
The concept of memory laws has been gaining attention for the past few years. It is commonly defined as legal provisions governing history, including repressive measures against the denial of past crimes. Memory laws also include stateapprovedinterpretations of crucial historical events, the law establishing state holidays and commemoration of victims of past atrocities. The laws have a big part in transition and reconciliation, however, they may also lead to a distortion of historical truth. The main purpose of the paper is to analyse the coexistence between memory laws and the right to the truth in the context of human rights violations and international crimes. For that reason, firstly, the legal nature of the truth and memory under international law is evaluated. Secondly, the Rwandan legal provisions on genocide are analysed and comments are made on the elements of the Rwandan traditions concerning the past. That example serves to show the danger of the politicization of memory laws. Finally, the paper is an attempt to answer the question whether the conjunction of the right to the truth and memory laws is necessary.